CONVECTIVE HEAT EXCHANGE ON THE LATERAL SURFACE OF A RELATIVELY LONG CYCLONE CHAMBER - E. N. Saburov; A. N. Orehov; D. A. Onokhin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The high-turbulent swirling flows of heat carrier that are created by a cyclone chamber are used in industry. They make it possible to intensify processes of heat and mass exchange. The results of an experimental study of convective heat transfer on the lateral surface of the active volume of a relatively long cyclone chamber considerably exceeding the length of the chambers that were used in previously performed studies are presented and analyzed in the article. Air supply in the swirler of the chamber was performed tangentially from diametrically opposite sides of the two input channels. The gas outlet was implemented from the opposite end. The heat transfer by convection to the swirling air flow was studied by the method of changing the state of aggregation of a heating agent – condensation of slightly superheated steam. Collecting condensate from the working section was made through a water seal for maintaining a constant pressure calorimeter. The amount of heat transferred during experiment was determined by weight of the collected condensate. The specific features of influence of geometrical characteristics of cyclone chamber on intensity of heat exchange are considered. In the experiments we varied the relative diameter of the outlet port of the chamber dвых and the relative area of the input channels fвх. Segmental construction of the chamber made it possible to move a calorimeter on its length. The local heat transfer coefficient was determined for various values of the dimensionless longitudinal coordinate z coinciding with the axis of the chamber, and counted from the back end of the swirler. The estimated equations of heat transfer obtained during the research are presented and recommended for use in practice of engineering. The considered problem is of an interest from the point of view of further research of aerodynamics and of convective heat transfer in a highly swirling flow cyclone devices, in order to improve the methods of their thermal and aerodynamic calculations.